Magnetic Resonance Imaging Biomarkers to Assess Substantia Nigra Damage in Idiopathic Rapid Eye Movement Sleep Behavior Disorder. Issue 11 (31st August 2017) - Pyatigorskaya, Nadya; Gaurav, Rahul; Arnaldi, Dario; Leu-Semenescu, Smaranda; Yahia-Cherif, Lydia; Valabregue, Romain; Vidailhet, Marie; Arnulf, Isabelle; Lehéricy, Stephane
Abstract: Objectives: Idiopathic rapid eye movement sleep behavior disorder (iRBD) is considered to be a prodromal stage of Parkinson's disease (PD). At PD onset, 40 to 70% of the dopaminergic neurons in the substantia nigra (SN) are already lost. Thus, milder SN damage is expected in participants with iRBD. We aimed to quantify SN damage in participants with iRBD using multimodal magnetic resonance imaging (MRI) and to determine biomarker efficacy in preclinical Parkinsonism. Methods: Nineteen participants with iRBD and 18 controls underwent 3-Tesla MRI, including diffusion tensor imaging, neuromelanin (NM)-sensitive imaging, and T2* mapping. Regions of interest in the SN area were drawn in NM-sensitive and T2-weighted images. The volume and normalized signal intensity in NM-sensitive images, R2*, and diffusion tensor measures were quantified in the SN. Additionally, two raters performed visual analysis of the SN using the NM-sensitive images. Results: Participants with iRBD showed a reduction in the NM-sensitive volume and signal intensity and a decrease in fractional anisotropy (FA) versus controls, but showed no differences in axial, radial, or mean diffusivity or in R2*. For NM-sensitive volume and signal intensity, the receiver operating characteristic analysis discriminated between participants with iRBD and controls with a diagnostic accuracy of 0.86 and 0.79, respectively, whereas the accuracy was 0.77 for FA. The three biomarkers had a combined accuracy of 0.92. The fraction of participants correctly characterized by visual assessment was 0.81. Conclusions: NM-sensitive imaging and FA allowed for the detection of SN damage in participants with iRBD with good diagnostic accuracy. These measures may represent valuable biomarkers for prodromal Parkinsonism.